Association Between Infectious Diseases and Exclusive Breastfeeding with Stunting Incidence Among Toddlers at Mamsena Public Health Center, Insana Barat District, North Central Timor Regency - Sanit, Roswita; Boeky, Daniela L A (Jurnal Pangan Gizi dan Kesehatan, 2025)
Background: Stunting is a chronic malnutrition problem caused by insufficient nutritional intake over a long period of time due to the provision of food that does not meet nutritional needs. Objectives: The purpose of this study was to determine the factors associated with the incidence of stunting at the Mamsena Health Center, Insana Barat District, North Central Timor Regency. Methods: This type of research is an analytical study (survey) using a case control research design. The sample in this study amounted to 106 respondents consisting of 53 case samples and 53 control samples with a ratio of 1: 1. The sampling technique used was simple random sampling with the Lottery technique. Data were obtained from interviews using questionnaires with chi square statistical tests and odds ratio values. Results: The results of the study showed that the variables of infectious diseases and history of exclusive breastfeeding were related to the incidence of stunting in toddlers at the Mamsena Health Center, Insana Barat District, North Central Timor Regency. Conclusion: History of Infectious Diseases and History of Exclusive Breastfeeding are related to the incidence of stunting at the Mamsena Health Center, Insana Barat District, North Central Timor Regency. Suggestions for the Mamsena Health Center, Insana Barat District to continue to provide counseling on stunting and the importance of health promotion related to the prevention of infectious diseases in children needs to be improved again to overcome the problem of stunting in toddlers.